Distinction between Pore Assembly by Staphylococcal α-Toxin versus Leukotoxins. (28th February 2007) - Joubert, Olivier; Voegelin, Joëlle; Guillet, Valérie; Tranier, Samuel; Werner, Sandra; Colin, Didier A.; Dalla Serra, Mauro; Keller, Daniel; Monteil, Henri; Mourey, Lionel; Prévost, Gilles
Abstract : The staphylococcal bipartite leukotoxins and the homoheptamericα -toxin belong to the same family ofβ -barrel pore-forming toxins despite slight differences. In theα -toxin pore, the N-terminal extremity of each protomer interacts as a deployed latch with two consecutive protomers in the vicinity of the pore lumen. N-terminal extremities of leukotoxins as seen in their three-dimensional structures are heterogeneous in length and take part in theβ -sandwich core of soluble monomers. Hence, the interaction of these N-terminal extremities within structures of adjacent monomers is questionable. We show here that modifications of their N-termini by two different processes, using fusion with glutathione S-transferase (GST) and bridging of the N-terminal extremity to the adjacentβ -sheet via disulphide bridges, are not deleterious for biological activity. Therefore, bipartite leukotoxins do not need a large extension of their N-terminal extremities to form functional pores, thus illustrating a microheterogeneity of the structural organizations between bipartite leukotoxins andα -toxin.